2019
DOI: 10.1155/2019/7401235
|View full text |Cite
|
Sign up to set email alerts
|

Cascade and Fusion of Multitask Convolutional Neural Networks for Detection of Thyroid Nodules in Contrast-Enhanced CT

Abstract: With the development of computed tomography (CT), the contrast-enhanced CT scan is widely used in the diagnosis of thyroid nodules. However, due to the artifacts and high complexity of thyroid CT images, traditional machine learning has difficulty in detecting thyroid nodules in contrast-enhanced CT. A fully automated detection algorithm for thyroid nodules using contrast-enhanced CT images is developed. A modified U-Net architecture of fully convolutional networks is employed to segment the thyroid region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…58 patients had accurate location of the lesion with an accuracy rate of 96.67%, which confirmed that the MSCT scan could clearly show the morphology and structure of the lesion, thereby providing intuitive clinical diagnosis. This was consistent with the research findings of Zhao et al [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…58 patients had accurate location of the lesion with an accuracy rate of 96.67%, which confirmed that the MSCT scan could clearly show the morphology and structure of the lesion, thereby providing intuitive clinical diagnosis. This was consistent with the research findings of Zhao et al [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…The recall rate is the ratio of the number of samples that are correctly predicted for the class to the total number of samples; it is also called the sensitivity or hit rate. Precision refers to the ratio of the number of category samples correctly predicted to the total number of samples predicted for that category [ 42 ]. The calculation methods for these indicators are as follows: where a is the number of samples misclassified, m is the total number of samples, TP is the number of positive samples correctly classified by the model, and FP is the number of negative samples misclassified by the model as positive samples.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…The work conducted by [83] adopted CT scans through CNN for detecting thyroid cancer metastasis, and their work reached an accuracy score of 0.904. Moreover, [84] fused two CNNs for CT scans to detect malignant thyroid nodules and obtained an accuracy of 95.73. While in this study, we obtained an accuracy of 0.966 for the hospital left-side CT scans and 0.970 for the right-side CT scans through the base model.…”
Section: Ctmentioning
confidence: 99%